Dental caries in children with organic damage of the nervous system and with orthopedic pathology - Приймак, Христина Василівна (Actual Dentistry, 2019)
The purpose of the research is to study the prevalence and intensity of tooth decay, as well as the level of oral hygiene in children with organic lesions of the central nervous system and with orthopedic pathology. Material and methods. 153 children were examined: 122 (79.7 %) children with infantile cerebral palsy (CP), 31 (20.3 %) children with orthopedic pathology and 80 practically healthy children. Children with CP were divided into groups according to the Gross Motor Function Classification System. Results. The mean values of caries intensity in these groups were respectively 6.27±1.19; 4.73±1.85, and 2.72±1.17. Caries intensity in children with cerebral palsy increases with the severity of impaired motor functions. The index of oral hygiene in children with cerebral palsy was 2.0 times higher compared to index in healthy children (2.00±0.25 vs. 0.98±0.26; p = 0.0066). Conclusions. The intensity of tooth decay in children with organic lesion of the nervous system is significantly higher in comparison with somatically healthy children, and increases, depending on the severity of motor disorders. Key words: children, infantile cerebral palsy, musculoskeletal system disorders, dental caries, oral hygiene.